2016
DOI: 10.1103/physrevlett.116.063902
|View full text |Cite
|
Sign up to set email alerts
|

Ultrabroad Terahertz Spectrum Generation from an Air-Based Filament Plasma

Abstract: We have solved the long-standing problem of the mechanism of terahertz (THz) generation by a two-color filament in air and found that both neutrals and plasma contribute to the radiation. We reveal that the contribution from neutrals by four-wave mixing is much weaker and higher in frequency than the distinctive plasma lower-frequency contribution. The former is in the forward direction while the latter is in a cone and reveals an abrupt down-shift to the plasma frequency. Ring-shaped spatial distributions of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
125
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 224 publications
(128 citation statements)
references
References 34 publications
2
125
0
1
Order By: Relevance
“…THz emission from interaction of ionizing intense laser pulses with gases is a promising approach for more compact broadband THz sources. Recently, various theoretical and experimental efforts have been made in this direction [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…THz emission from interaction of ionizing intense laser pulses with gases is a promising approach for more compact broadband THz sources. Recently, various theoretical and experimental efforts have been made in this direction [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Originally, fourwave mixing (FWM) rectification via third-order nonlinearity of the neutral atoms has been suggested as the THz generating mechanism in this case [10]. However later, it has been shown that contributions from FWM are much weaker than those from mechanisms based on excitation of the laser-induced plasma [16,20,23]. In particular, the ionization current (IC) mechanism proposed in [11] has been accepted as the major contributor to THz radiation from such a two-color pump, and this mechanism may also contribute for single-color pulses [21]: The extrema of the first and the second half-laser-cycle create two bunches of charge due to tunnel ionization.…”
Section: Introductionmentioning
confidence: 99%
“…For plasma detection, an intense gating pulse of frequency ω is focused to generate a second gas plasma and overlapped with the THz radiation between a pair of biased electrodes [269]. The mechanisms of THz generation are still under active investigation, but involve a combination of four-wave mixing, asymmetric photo-induced currents, and current oscillations [272]. The broadband pulses from two-color plasma filamentation are attractive for linear spectroscopic applications, as they provide continuous coverage from the microwave to the mid-infrared regions of the spectrum.…”
Section: Specific Implementationsmentioning
confidence: 99%
“…Figures 1(b,c,d) detail the THz spectra computed at the distance of maximum THz field production, i.e., where the on-axis THz fields attain their maxima. Because an important question has been the role of Kerr-induced four-wave mixing compared to that of photocurrents [7], Figs. 1(b,c,d) also compare the spectra computed with or without the plasma terms before the linear focus.…”
Section: Thz Spectra and Supercontinuum Generation Of Mid-and Far-infmentioning
confidence: 99%